Optical Power Transient Suppression by a Dynamic Broadband Attenuator Based on the Raman Effect - Holtmannspötter, Michael; Schmauß, Bernhard (Optical Fiber Communication 2008, 2008)
An optical attenuator based on the Raman Effect is presented which is shown to provide dynamic and broadband suppression of channel power transients in WDM transmission systems, without affecting the normal operation mode. ©2007 Optical Society of America.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.optica